Boedo "Circens": Leónidas Barletta, Raúl González Tuñón, and the Limits of Tradition. - Borge, Jason (Hispanic Review)
The circus and circensian practices lend themselves particularly well to the Latin American avant-gardes as privileged proletarian spaces encompassing both the ''crafty'' extreme of carnival—in Bakhtin's sense of subversive and artisan—as well as the commercial, technological aspects of the emerging mass media. This article focuses on the circus as a key link between traditional and modern culture in early twentieth-century Argentina. In particular, it examines the writing of Leónidas Barletta, Rúl González Tuñón, both figures loosely associated with the avant-garde Boedo movement. In the work of these writers, I argue, the circus operates primarily metonymically rather than metaphorically: through a series of interventions, principally Tuñón's early poems and Barletta's novel Royal Circo, the working-class suburb of Buenos Aires is laid out as a living theater of marginality in which the circus performs a central role. In his novel, Barletta sees the circensian as a site of greed and hunger in need of either liquidation or refinement--the latter option put to practice in Barletta's later work as founder and director of the influential Teatro del Pueblo. Tuñón, on the other hand, reconstitutes the circensian as a vital ''osmotic'' space between memory and modernity, in the process showing how apparently marginal cultural practices could be reconstituted through literary expression.